Chemical characterization of marine fish of low‑commercial value and development of fish burgers - Pires, Danielle Regis; Jamas, Amanda Lima Albuquerque; Amorim, Elizete; de Azevedo-Meleiro, Cristiane Hess; Silva, Pedro Paulo de Oliveira; de Oliveira, Gesilene Mendonça (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to perform the chemical characterization of marine bonefish (Albula vulpes) and the development of fish burgers. Three formulations of fish burgers were prepared, containing 5, 8, and 10% cassava starch and functional ingredients (onion, garlic, and ground white pepper). Proximate composition, microbiological and pH analyses of the raw material, and fish burgers were performed, as well as the sensory analyses of the fish burgers. The yield and nutritional value of bonefish was found to be comparable with those of species of commercial value, with high-protein and low-lipid contents. The protein content of the fish burgers varied from 17.52 to 19.40 g 100 g-1 (raw), and from 20.74 to 24.25 g 100 g-1 (grilled); and the lipid contents ranged from 0.20 to 0.73 g 100 g-1 (raw), and from 0.36 to 0.77 g 100 g-1 (grilled). In the sensory tests, the formulations received scores between six and seven on the nine-point hedonic scale. Acceptance indexes were higher than 70% for all the assessed attributes. Therefore, the use of this underutilized species proves to be feasible.